Use of Mixed Language Codes in Da’wah Ustaz Hanan Attaki on Social Media (Sociolinguistic Studies) - Nikmah, Faridhatun (Proceeding International Conference on Science and Engineering, 2020)
This study aims to explain the mixed code of language and the effectiveness of da’wah on social media. The method used in this study is descriptive qualitative by describing the mix of language codes used by Ustaz Hanan Attaki and the effectiveness of da’wah on social media. The data source in this study is a transcript of Ustaz Hanan Attaki’s lecture. Data collection is obtained by listening to video shows, recording data in the form of transcripts, classification by type, and data analysis. The results of the study show that (1) Ustaz Hanan Attaki classifies mixed language codes into two, namely inter-internal and external code mixing, and (2) Ustaz Hanan Attaki’s preaching on social media is very effective from a sociolinguistic perspective.